(untitled) (Academicia Globe: Inderscience Research, 2021)
In an emerging market economy, investment plays an important role. This article analyzes the ways to attract investment, the opportunities of Uzbekistan to increase investment attractiveness and the assistance provided by the state in this direction. Innovative ways to attract investment are described in detail. That is, the impact of foreign investment on the development of the digital economy in the country has been studied. In addition, proposals have been developed to increase the efficiency of foreign investment in the development of the digital economy and increase the volume of foreign investment entering the economy.